A Review on Zakat Payments by Islamic Banks in Malaysia - Samsuwatd Zuha Mohd Abbas; Saliza Sulaiman; Noorbijan Abu Bakar (International Journal of Zakat, 2018)
Zakat plays an important role in the economic development of the ummah. In line with Shariah requirements, the responsibility of paying zakat does not only lie in the Muslim individuals but also businesses, specifically Islamic banks. Islamic Banks exist to fulfil the financial (economic) needs of Muslims within the confines of the Islamic faith. This study aims to analyse the payment of zakat made by the Islamic Banks in Malaysia by firstly, examining the various methods adopted by the Islamic banks and secondly, comparing the existing method of zakat computation. A total of 16 Islamic banks are selected and the financial statements are reviewed from the year 2013 till 2017. The results of the study show that most of the Islamic banks adopted the two methods recommended by JAKIM and both methods show similar results. The results also show an underpayment of zakat by the selected Islamic bank. Further the study found that the detail computation of zakat is not disclosed in the financial statements and hence the study could not identify the adjustments for the zakat computation for all the Islamic banks.